Effect of Body Weight Uniformity on the Productivity of Broiler Breeder Hens - Abbas, S.A.; Elseid, A. A. Gasm; Ahmed, M-K.A. (International Journal of Poultry Science, 2010)
Measurements on hen-day and hen-housed egg production, hatchability, fertility, total hatching eggs, mortality and cracked eggs were made on eight flocks belonging to the Arab Company for Livestock Investment and Development. There were 6000 females and 600 male parent broilers in each flock. Uniformity was calculated by taking a random sample of 7% of the birds in each pen and weighting them on a weekly basis. The flocks were assigned to uniformity groups ranging from 55-80%. The high uniformity group (75-80%) consistently had the highest hen-day and hen-house production over all ages, while the low uniformity group had the lowest hen-day production. The analysis of variance showed that effects of age and uniformity group on all studied traits were highly significant. The effect of age x uniformity group was significant only for total hatched eggs. Percentage hatchability of settable eggs varied from 69.19±1.93 in the 55-59% group to 83.93±1.65 in the 75-80%. The highest levels of uniformity had the highest percentage of cracked eggs (0.30±0.01), while the medium range of uniformity had the lowest percentage of cracked eggs (0.182±0.011 in the 65-69% group). The highest fertility (86.53±1.56) was found in the 65-69% group. The study demonstrates the importance of controlling body weight and the use of restricted feeding to achieve optimum production and fertility in broiler breeder hens.